Quality of cassava flours sold at open markets in the City of Codó state of Maranhão, Brazil (Research, Society and Development, 2021)
Cassava has a fundamental role for human consumption, mainly in the form of flour, and is part of the daily meals of the population in the North and Northeast of the country. Due to its high consumption in the state of Maranhão, the present study aimed to evaluate the quality of cassava flours sold in open markets in the city of Codó state of Maranhão, Brazil. Analyzes of dirt and foreign materials, counting molds and yeasts were carried out, with subsequent verification of the presence of fungi of the genera Aspergillus and Penicillium and physical-chemical analyzes in 17 samples of cassava flour. The data obtained were subjected to analysis of variance and the means compared using the Tukey test being p> 0.05. In the results of the search for dirt and foreign materials, all samples showed physical contaminants, being in disagreement with the legislation. In the mold and yeast count, 58.82% of the samples had a high count. As for the presence of the genera of fungi, Aspergillus was identified in 100% of the samples and the Penicillium genus in 41.17%. In the physical-chemical analysis, most flours obtained moisture contents within those established by IN nº 52/2011, in the ash parameter, only the F16 sample was not in conformity, in the acidity parameter, high and low acidity flours were obtained. It was concluded that the samples were non-compliant with the presence of physical and microbiological contaminants, being a possible risk to consumers' health. The physical-chemical characteristics were mostly satisfactory, as the percentages were within the standards established by legislationIncluir o resumo em inglês.